The role of the gut microbiome and microbial metabolism in mediating opioid-induced changes in the epigenome - Kolli, Udhghatri; Roy, Sabita (Frontiers in Microbiology, 2023)
The current opioid pandemic is a major health crisis in the United States effecting millions of people, posing significant health and socio-economic burden. Preclinical and clinical research in the past few decades have delineated certain molecular mechanisms, identified various genetic, epigenetic, environmental factors responsible for opioid use associated pathophysiology and co-morbidities. Opioid use induced epigenetic modifications are identified as one of the important factors that mediate genetic changes in brain regions controlling the reward and drug seeking behaviors and also implicated in the development of tolerance. Recently, it has been shown that opioid use results in microbial dysbiosis leading to gut barrier disruption driving systemic inflammation impacting perception of pain, development of analgesic tolerance and behavioral outcomes. In this review we highlight the possible role of microbiota and microbial metabolites in mediating the epigenetic modifications induced by opioid use.